Negative and positive effects of transport on environment - Švadlenka, Libor (Univerzita Pardubice, 2010)
The paper deals with negative and positive effects of transport on environment. The society, as a bearer of costs on environment protection does not represents homogenous unit. In term of transport costs allocation the society can be split on society sphere (environment protection costs especially bear public service organisations and civil service authorities) and on individual sphere (majority of costs on environment protection bear in essence individuals). Finally the paper deals with the trends of transport in relation to environment including the problem of financing the external costs of transport. The article is published within the solution of research proposal VZ-MSM 0021627505 „The transport systems theory“.
Keywords: environment; transport; costs; pollution; subsidies; internalization